Time fractional and space nonlocal stochastic nonlinear Schrödinger equation driven by Gaussian white noise. Issue 2 (4th March 2019) - Liang, Jiarui; Shen, Tianlong; Qian, Xu; Song, Songhe
Abstract: We present the time-spatial regularity of the nonlocal stochastic convolution for Caputo-type time fractional nonlocal Ornstein–Ulenbeck equations by the generalized Mittag–Leffler functions and Mainardi function, and establish the existence and uniqueness of mild solutions for time fractional and space nonlocal stochastic nonlinear Schrödinger equation driven by Gaussian white noise. In addition, the global mild solution is also shown.